Method for making paper and paperboard
By reacting with microcellulose compounds in fiber suspensions to form paper or paperboard with improved drainage and dry strength properties, the negative impact of microcellulose compounds on drainage performance in the prior art is solved. Efficient papermaking process improvement has been achieved.
Patent Information
- Application Number
- CN202280063483.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-09-27
- Filing Date
- 2022-09-21
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-09-21
AI Technical Summary
The prior art has shortcomings in improving drainage performance and processability during papermaking, especially when the addition of microcellulose compounds will have a negative impact on drainage performance, and traditional methods are difficult to effectively improve the dry strength and productivity of paper or cardboard.
Polymer P3 is prepared by reacting an isocyanate-functionalized polymer with a microcellulose compound in a fiber suspension and injecting it into the fiber suspension to form paper or paperboard with improved drainage and dry strength properties. The process includes adding alkali metal and/or alkaline earth metal hydroxide to polymer P1 within 10 seconds to 60 minutes to obtain isocyanate functionalized polymer P2, followed by reaction with the microcellulose compound to form P3, and at the beginning of the reaction Re1 Inject fiber suspension within 24 hours.
The drainage performance and dry strength of paper or cardboard are significantly improved, while reducing the use of microcellulose, improving the productivity and finished product quality of the papermaking process.
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing paper or paperboard having improved drainage and processability. More specifically, the subject of the invention is a process comprising the production of a polymer obtained by isocyanate functionalization and addition of a microcellulose compound before adding the polymer to a fiber suspension for the production of paper or paperboard.
[0002] The invention also features subject paper and paperboard obtained by this process having improved physical properties. Background Art
[0003] The paper industry is constantly seeking to optimize its manufacturing processes, more particularly in terms of output, productivity, cost reduction and quality of the finished product.
[0004] The use of polymers as dry strength agents, water drainage agents and machinability agents has been widely described.
[0005] Water removal performance (or drainage) refers to the ability of a fiber mat to evacuate or drain the maximum amount of water before drying out. Improved drainage performance means energy savings and increased production capacity.
[0006] Processability refers to optimizing the operation of the paper machine by increasing productivity through better drainage on the table, better drying in the press section, reduced breakage through greater circuit cleanliness and reduced deposits.
[0007] US2015 / 041089 discloses polymer-grafted nanocrystalline cellulose that improves the wet strength, dry strength and drainage retention properties of paper substrates. The synthesis of this polymer-grafted nanocrystalline cellulose does not involve the formation of isocyanate bonds; it involves polymerizing monomers in the presence of nanocrystalline cellulose (5-10 nm diameter and 100-500 nm length). As clearly defined in paragraphs
[0011] and
[0047] of US2015 / 041089, drainage retention refers to the retention of solids, more specifically small solids such as fine particles, fillers or nanocrystalline cellulose, during the drainage of a liquid medium from a paper substrate. This is evidenced by a reduction in turbidity. According to an example of US2015 / 041089, the nanocrystalline cellulose accounts for about 4% by weight of the polymer. US2015 / 041089 does not seek to improve dewatering performance during the papermaking process.
[0008] It is known that microcellulose compounds improve the physical properties of paper when added to pulp (dosed at about 1-2% by weight). However, they can have a negative impact on drainage, ie dewatering properties.
[0009] Microcellulose compounds are usually in the form of pulp (containing 3% by weight of fibers) and have thickening properties. Therefore, it is not logistically feasible to incorporate them directly into polymer solutions (such as polyvinylamine) at the production site. Summary of the invention
[0010] Surprisingly, the Applicant has found that a papermaking process using a polymer resulting from the functionalization of an isocyanate and the addition of a microcellulose compound just upstream of the injection into a fiber suspension, advantageously a suspension of cellulose fibers, results in improved drainage and dry strength properties with a low metering (low dosage) of microcellulose relative to the pulp.
[0011] More precisely, the invention relates to a process for making paper or board from a fiber suspension, advantageously a suspension of cellulose fibers, during which a water-soluble polymer P1 comprising at least one nonionic monomer chosen from acrylamide, methacrylamide, N,N-dimethylacrylamide and acrylonitrile is subjected to a reaction Re1 to obtain a polymer P2, said polymer P2 is then subjected to a reaction Re2 to obtain a polymer P3, said polymer P3 being injected into the fiber suspension within 24 hours of the start of the reaction Re1,
[0012] - reaction Re1 comprises adding an alkali metal and / or alkaline earth metal hydroxide and an alkali metal and / or alkaline earth metal hypohalite to the polymer P1 after 10 seconds to 60 minutes to obtain an isocyanate-functionalized polymer P2,
[0013] - Reaction Re2 comprises the preparation of the polymer P3 by reaction between a microcellulose compound and a P2 polymer comprising isocyanate functional groups.
[0014] In other words, the method for producing paper or board from a fiber suspension according to the invention comprises the following steps:
[0015] a) injecting the polymer P3 into a fiber suspension, advantageously a suspension of cellulose fibers,
[0016] b) forming into paper or paperboard,
[0017] c) drying the paper or paperboard,
[0018] Prior to step a), a polymer P3 is prepared from a water-soluble polymer P1 of at least one nonionic monomer selected from acrylamide, methacrylamide, N,N-dimethylacrylamide and acrylonitrile according to reactions Re1 to Re2:
[0019] - Reaction Re1: Preparation of a polymer P2 comprising isocyanate functional groups by reaction between (i) an alkali metal hydroxide and / or an alkaline earth metal hydroxide, (ii) an alkali metal subhalide and / or an alkaline earth metal subhalide and (iii) a polymer P1 for 10 seconds to 60 minutes,
[0020] - Reaction Re2: Preparation of polymer P3 by reaction between (iv) a microcellulose compound and (v) a polymer P2 comprising isocyanate functional groups.
[0021] The process preferably does not have any decarboxylation step after reaction Re1 and before reaction Re2. A decarboxylation step after reaction Re1 and before reaction Re2 would actually reduce the number of isocyanate functional groups available to react with the microcellulose. The process can also be carried out without any decarboxylation step after reaction Re2, even if the isocyanate functional groups remain on the polymer P3.
[0022] In the following description and claims, all terms starting with gt -1 or kg.t -1 The polymer dosages indicated are all given as weight of polymer per ton of dry matter. The dry matter is the dry extract obtained after evaporation of water from the fiber suspension used in the process for making paper or board. The dry matter advantageously consists of cellulose fibers and fillers. The dry matter does not include microcellulose compounds of P3 polymers. The term "cellulose fibers" includes any cellulose entity, including fibers, fine fibers, microfibers or nanofibers. The fiber suspension refers to a thick stock or a thin pulp based on water and cellulose fibers. The thick stock, which is generally greater than 1% by mass of dry matter, or even greater than 3%, is located upstream of the mixing pump (fan pump). The thin stock, which is generally less than 1% by mass of dry matter, is located downstream of the fan pump.
[0023] The term "polymer" refers to both homopolymers and copolymers of at least two different monomers.
[0024] Amphoteric polymers are polymers which contain cationic and anionic charges, preferably the anionic charges are as numerous as the cationic charges.
[0025] As used herein, the term "water-soluble polymer" refers to a polymer that is soluble in water at 20 g / L when stirred at 25°C for 4 hours. -1 A polymer that, when dissolved in deionized water at a concentration of , produces an aqueous solution free of insoluble particles.
[0026] Numerical ranges include lower limits and upper limits. Thus, the numerical ranges "between 0.1 and 1.0" and "from 0.1 to 1" include the values 0.1 and 1.0.
[0027] The water-soluble polymer P1 is a polymer of at least one nonionic monomer selected from acrylamide, methacrylamide, N,N-dimethylacrylamide, and acrylonitrile. Preferably, polymer P1 contains at least 50 mol % of at least one of these nonionic monomers.
[0028] The water-soluble polymer P1 can be prepared by any conventional polymerization technique, for example by solution polymerization, gel polymerization, emulsion polymerization (water-in-oil or oil-in-water). Typically, the water-soluble polymer P1 is prepared at a temperature preferably greater than the temperature of reaction Re1 and / or greater than the temperature of reaction Re2.
[0029] The polymer P1 may also contain anionic monomers and / or cationic monomers and / or zwitterionic monomers. The polymer P1 is advantageously free of nonionic monomers other than those selected from acrylamide, methacrylamide, N,N-dimethylacrylamide and acrylonitrile.
[0030] The anionic monomer is preferably selected from the group comprising: monomers having carboxylic acid functional groups and their salts, including acrylic acid, methacrylic acid, itaconic acid, maleic acid; monomers having sulfonic acid functional groups and their salts, including acrylamido tert-butylsulfonic acid (ATBS), allylsulfonic acid and methallylsulfonic acid and their salts; and monomers having phosphonic acid functional groups and their salts.
[0031] Typically, the salts of the anionic monomers of polymer P1 are alkali metal, alkaline earth metal or ammonium (preferably quaternary ammonium) salts.
[0032] Preferred monomers belonging to this category are, for example, quaternized dimethylaminoethyl acrylate (DMAEA), quaternized dimethylaminoethyl methacrylate (DEAEMA), dimethyldiallylammonium chloride (DADMAC), acrylamidopropyltrimethylammonium chloride (APTAC) and methacrylamidopropyltrimethylammonium chloride (MAPTAC) and mixtures thereof.
[0033] Advantageously, the cationic monomers of polymer P1 have halide ions, preferably chloride ions, as counterions.
[0034] The zwitterionic monomer is preferably selected from the group comprising: sulfobetaine monomers such as sulfopropyldimethylammoniumethyl methacrylate, sulfopropyldimethylammoniumpropylmethacrylamide or sulfopropyl 2-vinylpyridinium; phosphobetaine monomers such as phosphoethyltrimethylammoniumethyl methacrylate; and carboxybetaine monomers.
[0035] Preferably, the water-soluble polymer P1 is nonionic. In other words, it preferably comprises only nonionic monomers. Even more preferably, the water-soluble polymer P1 is an acrylamide or methacrylamide homopolymer.
[0036] The polymer P1 may be linear, structured or crosslinked. In particular, the crosslinking agent capable of structuring may be selected from sodium allyl sulfonate, sodium methallyl sulfonate, sodium methallyl disulfonate, methylenebisacrylamide, triallylamine and triallylammonium chloride.
[0037] The structuring of polymer P1 can also be obtained with at least one polyfunctional compound containing at least 3 heteroatoms selected from N, S, O, P and each having at least one mobile hydrogen. This polyfunctional compound can in particular be a polyethyleneimine or a polyamine.
[0038] The weight average molecular weight of polymer P1 is advantageously between 100,000 and 20 million, preferably between 250,000 and 5 million Daltons.
[0039] According to the invention, the weight average molecular weight of polymer P1 is determined by measuring the intrinsic viscosity. The intrinsic viscosity can be measured by methods known to those skilled in the art and can be calculated in particular from the reduced viscosity values of different concentrations by a graphical method, which consists in plotting the reduced viscosity values (on the ordinate axis) as a function of the concentration (on the abscissa axis) and extrapolating the curve to zero concentration. The intrinsic viscosity values are read on the ordinate or using the least squares method. The weight average molecular weight can then be determined by the well-known Mark-Houwink equation:
[0040] [η] = KM α
[0041] [η] represents the intrinsic viscosity of the polymer determined by the solution viscosity measurement method,
[0042] K represents the empirical constant,
[0043] M represents the molecular weight of the polymer,
[0044] α represents the Mark-Houwink coefficient,
[0045] α and K depend on the specific polymer-solvent system. Tables known to the person skilled in the art give the values of α and K as a function of the polymer-solvent system.
[0046] Reaction Re1 comprises adding (i) an alkali metal hydroxide and / or an alkaline earth metal hydroxide and (ii) an alkali metal subhalide and / or an alkaline earth metal subhalide to (iii) polymer P1 to obtain an isocyanate-functional polymer P2.
[0047] Advantageously, the alkali metal hydroxide is soda (sodium hydroxide) and the alkali metal hypohalide is sodium hypochlorite.
[0048] The reaction Re1 is advantageously carried out on polymer P1 in aqueous solution at a concentration by mass of from 0.5 to 20%, preferably from 1 to 10%, of polymer P1.
[0049] Preferably, for the Re1 reaction, the coefficient α = the number of moles of subhalide (alkali metal and / or alkaline earth metal) / the number of moles of non-ionic monomer of polymer P1 is 0.1 to 1.0, and the coefficient β = the number of moles of hydroxide (alkali metal and / or alkaline earth metal) / the number of moles of subhalide (alkali metal and / or alkaline earth metal) is 0.5 to 4.0.
[0050] The alpha coefficient makes it possible to determine the amount of isocyanate functions formed by the nonionic monomers (acrylamide, methacrylamide, N,N-dimethylacrylamide and acrylonitrile) of polymer P1 during reaction Re1. Here, this alpha coefficient is not the alpha coefficient of the Mark-Hawk equation.
[0051] The Re1 reaction is advantageously carried out at a temperature of 30°C to 60°C, more advantageously 40°C to 50°C.
[0052] Thus, according to one embodiment, the Re1 reaction can be carried out at a temperature of 30°C to 60°C, in the presence of an alpha coefficient of 0.1 to 1.0, from an aqueous solution with a mass concentration of polymer P1 of 0.5 to 20%, the alpha coefficient being the ratio of the number of moles of subhalide to the number of moles of nonionic monomer of polymer P1.
[0053] The Re2 reaction involves the preparation of the polymer P3 by reaction between a microcellulose compound and a polymer P2 comprising isocyanate functional groups.
[0054] Advantageously, during the Re2 reaction, the microcellulose compound is in the form of a suspension in water.
[0055] The Re2 reaction is advantageously carried out on polymer P2 at a mass concentration of 0.5 to 20%, preferably 1 to 5%, of polymer P2 in aqueous solution.
[0056] Advantageously, the Re2 reaction is carried out in the absence of a compound having at least one aldehyde function or a compound capable of generating at least one aldehyde function.
[0057] The Re2 reaction is preferably carried out by adding the microcellulose compound directly to the reaction medium (aqueous solution) resulting from the Re1 reaction.
[0058] The polymer P3 is injected into the fiber suspension within 24 hours after the start of reaction Re1. In fact, the isocyanate groups formed during reaction Re1 are short-lived species that are very reactive and unstable. A total reaction time of more than 24 hours will reduce (ultimately to zero) the amount of isocyanate functional groups that are readily reactive with the microcellulose.
[0059] The Re2 reaction is advantageously carried out at a temperature ranging from 10°C to 60°C, preferably from 20°C to 40°C.
[0060] Without wishing to be bound by any theory, it appears that during the Re2 reaction the isocyanate functions of the polymer P2 react with the OH functions of the microcellulose compound, for example forming carbamate functions of -NH-C(=O)-O. The Re2 reaction does not require any pretreatment of the microcellulose.
[0061] Due to the control of the isocyanate functional groups formed, the present invention allows the functionalization of the polymer with a predetermined amount of microcellulose. This is in contrast to US2015 / 041089, which allows the functionalization of nanocrystalline cellulose with a predefined amount of polymer chains, as it requires pre-functionalization of the nanocrystalline cellulose with reactive groups.
[0062] The present invention thus provides a convenient method for functionalizing polymers with microcellulose, since the process can be carried out directly in the paper mill from the paper machine. The present invention allows the formation of polymer P1 (monomers, molecular weight, structure) to be controlled before reaction Re1, which is not possible if polymer P1 is prepared in the presence of cellulose.
[0063] Preferably, the microcellulose compound is selected from nanofibrillated cellulose, microfibrillated fibers, nanocrystalline cellulose, nanocellulose.
[0064] For the Re2 reaction, preferably 10% to 100% of the microcellulose compound is added to the polymer P2, more preferably 10% to 50%, relative to the weight of the polymer P2.
[0065] According to a preferred embodiment, the polymer P3 is introduced into the white water and / or the thick stock and / or into the mixture formed from white water and the thick stock after homogenization of the fiber suspension in the blower pump.
[0066] Advantageously, the polymer P3 can also be introduced into the papermaking process at the forming wire, for example by spraying or in the form of a foam, or at the size press (coater).
[0067] Advantageously, 0.1 to 10 kg.t. of -1 , preferably 0.2 to 5.0 kg.t -1 of polymer P3.
[0068] The polymer P3 is preferably introduced into the papermaking process immediately after reaction Re2, preferably without any purification step.
[0069] The fiber suspension includes different cellulose fibers that may be used: virgin fibers, recycled fibers, chemical pulp, mechanical pulp. The fiber suspension also includes the use of these different cellulose fibers and all types of fillers, such as TiO2, CaCO3 (crushed or precipitated), kaolin, organic fillers and mixtures thereof.
[0070] Polymer P3 can be used in the papermaking process in combination with other products, such as inorganic or organic coagulants, dry strength agents, wet strength agents, natural polymers such as starch or carboxymethyl cellulose (CMC), inorganic microparticles such as bentonite microparticles and colloidal silica microparticles, organic polymers of any ionic nature (non-ionic, cationic, anionic or amphoteric) and which can be (but not limited to) linear, branched, cross-linked, hydrophobic or associative. DETAILED DESCRIPTION
[0071] The following examples illustrate the invention without limiting its scope.
[0072] Procedure for application testing:
[0073] a) Type of pulp used
[0074] Recycled fiber pulp:
[0075] Wet pulp is obtained by disintegrating dry pulp to obtain a final moisture concentration of 1% by weight. It is a pH neutral pulp made from 100% recycled paperboard fibers.
[0076] b) Drainage performance assessment (DDA)
[0077] The DDA ("Dynamic Drainage Analyser") enables the automatic determination of the time (in seconds) required to drain the fiber suspension under vacuum. To the wet pulp (0.6 L of 1.0 wt. % pulp) in the DDA drum was added the polymer under stirring at 1000 rpm:
[0078] -T=0s: Pulp stirring
[0079] -T=20s: Add additives
[0080] -T = 30s: stop stirring and keep at 200mbar (1bar = 10 5 Pa) under vacuum for 70 seconds
[0081] The pressure under the paper sheet is recorded as a function of time. When all the water has been drained from the fiber mat, air is passed through the mat, causing a sudden change in the slope of the curve representing the pressure under the paper sheet as a function of time. The time (in seconds) recorded at the sudden change in slope corresponds to the drainage time. The shorter the time, the better the vacuum drainage effect.
[0082] c) Performance under DSR application (dry strength), weight 90g.m -2
[0083] Remove the required amount of pulp to obtain a grammage of 90 g.m. -2 of paper.
[0084] Introduce wet pulp into the barrel of a dynamic molder and maintain stirring. Into this slurry are injected various components of the system according to a predetermined sequence. Typically, the contact time between each addition of polymer is 30 to 45 seconds.
[0085] The paper forming machine is made of an automatic dynamic forming machine: the absorbent paper and the forming paper sheets are placed in the tank of the dynamic forming machine, and then the tank is turned at 1000 rpm and a water wall is built. The treated pulp is spread on the water wall to form a fiber mat on the forming paper sheet.
[0086] Once the water was drained off, the fiber mat was collected, pressed at a pressure of 4 bar provided and then dried at 117° C. The paper sheets obtained were placed overnight in a room with controlled humidity and temperature (50% relative humidity and 23° C.). The dry strength properties of all paper sheets obtained by this procedure were then measured.
[0087] Rupture is measured according to TAPPI T403 om-02 with a Messmer Buchel M 405 Rupture Instrument. The results are expressed in kPa. Rupture Index, in kPa.m 2 / g is expressed by dividing this value by the grammage of the test paper sheet.
[0088] Test products in application trials:
[0089] Polymer P1
[0090] 310g of water are introduced into a 1-liter reactor equipped with a mechanical stirrer, a thermometer, a condenser and a nitrogen plunger. Use pH buffer (30% by weight of NaOH and 75% by weight of H3PO4) to adjust the pH of the reaction medium to 3.3. Use a water bath to heat the medium and maintain a temperature of 79 to 81°C. By pouring twice continuously, 400g of 50% acrylamide, 0.28g of 100% N, N-methylenebisacrylamide, 237.8g of water and 2.40g of 100% sodium methallyl sulfonate are mixed (pour 1), and continue for 180 minutes. Pour 2, 0.48g of 100% sodium persulfate and 48g of water are mixed and continue for 180 minutes. After the pouring process ends, the polymer is placed at 80°C for 120 minutes.
[0091] The pH of the obtained P1 polymer was 5.7, the concentration was 20% by weight, and the viscosity was 6000 cps.
[0092] Polymer P2
[0093] Prepare a 10% solution of P1, 20 g of P1 and 20 g of water. Heat the polymer to 50°C.
[0094] A mixture of 14.6% sodium hypochlorite and 30% sodium hydroxide was prepared, where for the Re1 reaction the alpha coefficient was equal to 0.5 and the beta coefficient was equal to 2. When the polymer P1 was at 50°C, the mixture of sodium hypochlorite and sodium hydroxide was added to P1. After 30 seconds of reaction, water (room temperature) was added. The P2 polymer was obtained.
[0095] Polymer P3
[0096] Three minutes after polymer P2 was obtained, 17.7 g of microfibrillated cellulose (3 wt% in water at 30° C.) and 15 g of water (room temperature) were added to carry out Re2 reaction, ie, microfibrillated cellulose was 15 wt% relative to polymer P2. Polymer P3-A was obtained.
[0097] Three minutes after obtaining polymer P2, 41.3 g of microfibrillated cellulose (3 wt% in water at 30° C.) and 30 g of water (room temperature) were added to carry out Re2 reaction, ie, 35 wt% of microfibrillated cellulose relative to polymer P2. Polymer P3-B was obtained.
[0098] Three minutes after obtaining polymer P2, 4.7 g of microfibrillated cellulose (3 wt% in water at 30° C.) and 5 g of water (room temperature) were added to carry out Re2 reaction, ie, 4 wt% of microfibrillated cellulose relative to polymer P2. Polymer P3-C was obtained.
[0099] Application testing:
[0100] In the following, MFC refers to microfibrillated cellulose
[0101] sample Drainage Burst index blank 25 2.35 P3-A(1.5kg / t) 18 2.9 P3-B(1.5kg / t) 22 2.8 P3-C 1.5kg / t 17 2.65 MFC(0.150kg / t) 26 2.4 MFC(0.350kg / t) 27 2.45 MFC(20kg / t) 32 2.95
[0102] Table 1: Drained and dry strength values depending on the microfibrillated cellulose or polymer P3 in the pulp.
[0103] The addition of microfibrillated cellulose to the pulp resulted in a reduction in drainage. This was even more evident when the microfibrillated cellulose was measured at 20 kg / t, which gave the greatest improvement in bursting.
[0104] The process of the invention comprises adding polymers P3-A, P3-B or P3-C to the pulp, making it possible to obtain equivalent results in terms of improved bursting, while allowing a significant improvement in drainage and a reduction in the consumption of microfibrillated cellulose. For P3-C, where the weight % of MFC added for Re2 is lower than 10% (by weight relative to the weight of polymer P2), the improvement in bursting is lower than for P3-A and P3-B.
Claims
1. A process for producing paper or paperboard from a fiber suspension, comprising the following steps: a) injecting polymer P3 into the fiber suspension, b) forming into paper or paperboard, c) drying the paper or paperboard, Prior to step a), a polymer P3 is prepared from a water-soluble polymer P1 of at least one nonionic monomer selected from acrylamide, methacrylamide, N,N-dimethylacrylamide and acrylonitrile, Polymer P1 is subjected to Re1 reaction to obtain polymer P2, and then polymer P2 is subjected to Re2 reaction to obtain polymer P3, and within 24 hours after the start of Re1 reaction, polymer P3 is injected into the fiber suspension wherein the Re1 reaction comprises preparing a polymer P2 comprising isocyanate functional groups by reacting (i) an alkali metal hydroxide and / or an alkaline earth metal hydroxide, (ii) an alkali metal subhalide and / or an alkaline earth metal subhalide and (iii) a polymer P1 for a period of 10 seconds to 60 minutes, - wherein the Re2 reaction comprises the preparation of the polymer P3 by reaction between (iv) a microcellulose compound and (v) a polymer P2 comprising isocyanate functional groups.
2. The process according to claim 1, characterized in that The polymer P1 is nonionic.
3. The process according to claim 1 or 2, characterized in that The polymer P1 is a homopolymer of acrylamide or methacrylamide.
4. The process according to claim 1 or 2, characterized in that For the Re1 reaction, the coefficient α=moles of subhalide / moles of nonionic monomer of water-soluble polymer P1 is 0.1 to 1.0, and the coefficient β=moles of hydroxide / moles of subhalide is 0.5 to 4.
0.
5. The process according to claim 1 or 2, characterized in that: For the Re2 reaction, the microcellulose compound is selected from nanofibrillated cellulose, microfibrillated fibers, nanocrystalline cellulose, and nanocellulose.
6. The process according to claim 1 or 2, characterized in that For the Re2 reaction, 10% to 100% by weight of the microcellulose compound are added to the polymer P2, relative to the weight of the polymer P2.
7. The process according to claim 1 or 2, characterized in that After homogenization of the fiber suspension in the dilution pump, the polymer P3 is introduced into the white water and / or the thick stock and / or into a mixture of white water and thick stock.
8. The process according to claim 1 or 2, characterized in that During the Re2 reaction, the microcellulose compound is in the form of a suspension in water.
9. The process according to claim 1 or 2, characterized in that The Re2 reaction is carried out in the absence of a compound having at least one aldehyde function or a compound capable of generating at least one aldehyde function.
10. The process according to claim 1 or 2, characterized in that: -Re1 reaction is carried out at a temperature of 30°C to 60°C, in the presence of an alpha coefficient of 0.1 to 1.0, from an aqueous solution with a mass concentration of polymer P1 of 0.5 to 20%, the alpha coefficient being the ratio of the number of moles of subhalide to the number of moles of nonionic polymer monomer P1; The -Re2 reaction is carried out in the presence of the polymer P2 and 10 to 100% by weight of a microcellulose compound, relative to the weight of the polymer P2.
11. The process according to claim 1 or 2, characterized in that The process does not have any decarboxylation step after reaction Re1 and before reaction Re2.
12. The process according to claim 1 or 2, characterized in that The process does not have any decarboxylation step after reaction Re2.
13. The process according to claim 1 or 2, characterized in that For the Re2 reaction, 10% to 50% by weight of the microcellulose compound are added to the polymer P2, relative to the weight of the polymer P2.
14. The process according to claim 1 or 2, characterized in that 0.1 to 10 kg of polymer P3 per ton of dry matter of the fiber suspension are added to the fiber suspension, which is a suspension of cellulose fibers and filler in water.
15. The process according to claim 1 or 2, characterized in that 0.2 to 5.0 kg of polymer P3 are added to the fiber suspension, which is a suspension of cellulose fibers and filler in water, per ton of dry matter of the fiber suspension.
16. The process according to claim 1 or 2, characterized in that: - for the Re1 reaction, the coefficient α=moles of subhalide / moles of nonionic monomer of water-soluble polymer P1 is 0.1 to 1.0, the coefficient β=moles of hydroxide / moles of subhalide is 0.5 to 4.0, - for the Re2 reaction, the microcellulose compound is selected from nanofibrillated cellulose, microfibrillated fibers, nanocrystalline cellulose, nanocellulose, - for the Re2 reaction, 10 to 100 wt. % of a microcellulose compound is added to the polymer P2, relative to the weight of the polymer P2, The -Re1 reaction is carried out with an aqueous solution of polymer P1 having a mass concentration between 0.5% and 20% at a temperature between 30°C and 60°C.
